Morality, competition, and the firm : the market failures approach to business ethics - Heath, Joseph, 1967- (UK : Oxford University Press, 2014)
"In this collection of provocative essays, Joseph Heath provides a compelling new framework for thinking about the moral obligations that private actors in a market economy have toward each other and to society. In a sharp break with traditional approaches to business ethics, Heath argues that the basic principles of corporate social responsibility are already implicit in the institutional norms that structure both marketplace competition and the modern business corporation. In four new and nine previously published essays, Heath articulates the foundations of a "market failures" approach to business ethics. Rather than bringing moral concerns to bear upon economic activity as a set of foreign or externally imposed constraints, this approach seeks to articulate a robust conception of business ethics derived solely from the basic normative justification for capitalism. The result is a unified theory of business ethics, corporate law, economic regulation, and the welfare state, which offers a reconstruction of the central normative preoccupations in each area that is consistent across all four domains. Beyond the core theory, Heath offers new insights on a wide range of topics in economics and philosophy, from agency theory and risk management to social cooperation and the transaction cost theory of the firm"--
"The essays by Joseph Heath collected in this volume collectively present a program in business ethics that he calls the "market failures" approach. They develop a theoretical framework that lies between two opposing positions in business ethics -- on one hand the "stakeholder" theory, which identifies moral obligations within an organization by identifying its key groups, and the self-explanatory "shareholder primacy" theory. Heath's "market failures" approach lies between these approaches and argues that firms should be guided by the ideal of a perfectly competitive market, and that ethical behavior in this context consists primarily in refraining from taking advantage of imperfections in existing markets. Heath's approach puts particular emphasis on the market as a competitively structured interaction, with different duties owed to individuals inside and outside the firm, and explains why business managers cannot have fiduciary responsibilities toward every stakeholder group. His theory draws on recent work in adversarial ethics, welfare economics, agency theory, and the theory of the ferm, in order to provide an account of business ethics that can be integrated with recent thinking about corporate law and the normative basis of state regulation of the economy"--
Machine generated contents note: -- Acknowledgements -- Introduction -- Part 1: The Corporation and Society -- 1. A Market Failures Approach to Business Ethics -- 2. Stakeholder Theory, Corporate Governance and Public Management (with Wayne Norman) -- 3. Business Ethics Without Stakeholders -- 4. An Adversarial Ethic for Business: or, When Sun-Tzu met the Stakeholder -- 5. Business Ethics and the 'End of History' in Corporate Law -- Part 2: Cooperation and the Market -- 6. Contractualism: Micro and Macro -- 7. Efficiency as the Implicit Morality of the Market -- 8. The History of the Invisible Hand -- 9. The Benefits of Cooperation -- Part 3: Extending the Framework -- 10. The Uses and Abuses of Agency Theory -- 11. Business Ethics and Moral Motivation: a Criminological Perspective -- 12. Business Ethics After Virtue -- 13. Reasonable Restrictions on Underwriting -- Bibliography -- Index.
Includes bibliographical references (pages 373-394) and index.
Keywords: Business ethics; Profit -- Moral and ethical aspects; Competition; Corporations -- Moral and ethical aspects